2022
DOI: 10.3389/ijph.2022.1605048
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Coronavirus Disease 2019 Preventive Measures in a Representative Sample of the Population of the Canton of Vaud, Switzerland

Abstract: Objectives: We quantified adherence to COVID-19 preventive measures and explored associated factors, after the first and during the second Swiss epidemic waves.Methods: With an observational cohort study in a representative sample of individuals aged 15 years and more, we analysed the association between self-reported adherence to COVID-19 preventive measures (respect of simple hygiene rules; respect of social distancing rules; wearing a mask) and socio-demographic factors, the existence of a chronic disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…However, it only included young adults and used data collected during the early phase of the COVID-19 pandemic (until April 2020). Another cross-sectional study conducted in Switzerland found mixed results, showing higher compliance with respecting social distancing in people with higher education and higher compliance with wearing a mask in participants with a lower educational level [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it only included young adults and used data collected during the early phase of the COVID-19 pandemic (until April 2020). Another cross-sectional study conducted in Switzerland found mixed results, showing higher compliance with respecting social distancing in people with higher education and higher compliance with wearing a mask in participants with a lower educational level [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…We assessed whether participants’ EDI and educational level were associated with adherence to preventive measures using a multivariable mixed logistic regression model with person-specific random intercepts, reporting odds ratios (ORs) and 95% confidence intervals (CIs). We included the following covariates in our model based on findings of previous studies and background expert knowledge [ 7 , 27 30 ]: sex, age, canton, work situation (retired, in training/studying, working part- or full-time, non-working, other), self-reported comorbidities (cancer, diabetes, immunological diseases, hypertension, cardiovascular diseases, respiratory diseases), body mass index (BMI), smoking status (smoking daily, smoking occasionally, former smoker, never smoked), worries about the risk of being infected with SARS-CoV-2 (Likert scale from 1 to 5; 1 not worried at all, 5 extremely worried). These variables were all assessed at baseline.…”
Section: Methodsmentioning
confidence: 99%
“…The model was later expanded with two additional constructs to reflect the observations that health behaviors could be altered by external and internal cues that motivate one to adopt certain behaviors (cues to action) and the confidence in one's ability to successfully perform a behavior (self-efficacy) ( Rosenstock, Strecher, & Becker, 1988 ). The HBM has been shown to predict compliance with recommended practices to prevent COVID-19 infection during the early stages of the pandemic ( Alagili & Bamashmous, 2021 ; Badr et al, 2021 ; Butty et al, 2022 ; Guidry et al, 2021 ; Jose et al, 2021 ; Karimy et al, 2021 ; Mirzaei et al, 2021 ; Moghadam et al, 2022 ; Noghabi et al, 2021 ; Tong et al, 2020 ; Yan et al, 2021 ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“… Jang (2022) revealed that knowledge of the disease and acquaintance with related government policies lead to adequate compliance with preventive health guidelines. Several studies have used the health belief model (HBM) to show that people's beliefs about COVID-19, as measured by perceived susceptibility, perceived severity, perceived benefit, and perceived barriers, predict adherence to preventive measures ( Alagili & Bamashmous, 2021 ; Badr et al, 2021 ; Butty et al, 2022 ; Guidry et al, 2021 ; Jose et al, 2021 ; Karimy et al, 2021 ; Mirzaei et al, 2021 ; Moghadam, Zobeidi, Sieber, & Löhr, 2022 ; Noghabi, Mohammadzadeh, Yoshany, & Javanbakht, 2021 ; Tong, Chen, Yu, & Wu, 2020 ; Yan, Lai, Lee, & Ng, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] During the COVID-19 pandemic, risk perceptions were influenced by death rates, intensive care stays, and perceptions of high vulnerability among individuals or family members. People with chronic diseases [22,[25][26][27] and parents of high-risk children were shown to comply well with protective regulations. [23] Social norms, with poor compliance when only a few people abide measures, influenced the social acceptability of measures.…”
Section: Would People Comply With These Measures?mentioning
confidence: 99%